Interest in Entrepreneurship in Principal Leadership in Student Entrepreneurship - Andriadi, Dian; Wahyudi, Lutfi; Muazza, Muazza (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to analyze the role of school principals' leadership in increasing entrepreneurial interest in students. The research uses a descriptive qualitative approach with data collection techniques in the form of interviews, observations, document studies, and focus group discussions (FGD). The subjects of the study include school principals, teachers, students, and external parties involved in entrepreneurship programs. The results show that school principals play an important role in encouraging students' interest in entrepreneurship through transformative leadership. The strategies implemented include the integration of entrepreneurship education in the curriculum, the development of extracurricular activities, and cooperation with the business world.